Validity and reliability of an isometric row in quantifying maximal force production in collegiate rowers - Pineda, D.; Hudak, J.; Bingham, G. E.; Taber, C. B. (The Journal of Strength and Conditioning Research, 2023)
The objective of this study was to examine the relationship between a maximal isometric strength test with a maximal dynamic strength test. The main outcome was to evaluate the isometric test to determine if it was a valid and reliable measurement tool for testing and monitoring of rowing athletes. Collegiate Division 1 rowers were tested on measures of maximal dynamic and isometric strength on 2 occasions separated by 14 days. Thirty-two female athletes (age: 19.9 11.0 years; height: 168.2 ± 7.6 cm; body mass: 71.3 as13.2 kg) participated in this study. Although the isometric test had greater reliability, both tests displayed good-to-excellent reliability (intraclass correlation coefficient = 0.79-0.92). Strong correlations were present for the relationship between isometric and dynamic strength tests (r = 0.76-0.82, p = <0.001). The data indicate that the isometric row test is valid and reliable compared with dynamic testing and may be used in conjunction with dynamic testing in the evaluation of collegiate rowers.